Impact of nodular calcification on the outcomes of patients with acute coronary syndrome (ACS) treated with primary percutaneous coronary intervention (PCI). (14th October 2021) - Demuyakor, A; Hu, S; Koniaeva, E; Liu, M; Weng, Z; Zhao, C; Feng, X; He, L; Xu, Y; Zeng, M; Meng, W; Yi, B; et al.
Abstract: Background: Calcified plaque is thought to adversely impact clinical outcomes but the impact of nodular calcification after percutaneous coronary intervention (PCI) in patients with acute coronary syndrome (ACS) remains unclear. Purpose: This study sought to explore the impact of nodular calcification on the outcomes of patients undergoing percutaneous coronary intervention for acute coronary syndromes. Methods: Five-hundred culprit plaque with calcification were analysed from 495 ACS patients in whom PCI was performed. Plaques were divided into nodular calcification group (n=238) and non-nodular calcification group (n=262). Calcification is defined as an area with low back-scattering signal and a sharp border. Nodular calcification was defined as a protruding mass with an irregular surface, high backscattering, and signal attenuation on optical coherence tomography (OCT). Results: Patients with nodular calcification were older (p<0.001) and had lower left ventricular ejection fraction (p=0.006) compared to patients with non-nodular calcification. Lesion length (31 (25.2, 38.5) vs. 29 (22.8, 34.1), p<0.001) was longer in plaques with nodular calcification. A higher prevalence of superficial calcium (p<0.001) was observed in plaques with nodular calcification compared with non-nodular calcification group. Minimum stent area (MSA) (5.0 (3.9, 6.3) vs. 5.4 (4.2, 6.7), p=0.011) and stent expansion (70 (62.7, 81.8) vs. 75 (65.2, 86.6), p=0.004) were significantly smaller in the nodular calcification group than in the non-nodular calcification group. Independent predictors of nodular calcification were age (p<0.001) lesion length (p=0.002) and calcium depth (p<0.001). Conclusion: This study demonstrated that the presence of nodular calcification is associated with unfavourable outcomes with smaller minimum stent area and higher incidence of stent under expansion in patients with ACS treated with primary PCI. FUNDunding Acknowledgement: Type of funding sources: None.